V30 as a predictor for radiation-induced hypothyroidism: a dosimetric analysis in patients who received radiotherapy to the neck - (:unkn) unknown (BIOMED CENTRAL LTD, 2014)
Introduction: The purpose of this study is to evaluate the possible predictors of thyroid disorders after neck radiotherapy, with a focus on radiation dose-volume factors. Methods: Thyroid function was measured in 100 patients who had received radiotherapy to the neck, including the thyroid. All radiation-induced thyroid dysfunctions were determined with an endpoint of abnormal thyroid stimulating hormone (TSH), free triiodothyronine (fT3) and thyroxine (fT4) and thyroid peroxidase antibodies and (TPA). The total volume of the thyroid, mean radiation dose to the thyroid (Dmean) and thyroid volume percentage that received radiation doses of 10-50 Gy (V10-V50) were calculated in all patients. The evaluated risk factors for thyroid dysfunction included dose-volume parameters, sex, age, previous surgery, chemotherapy and comorbidity. Results: There were 52 patients with hypothyroidism and V30 (p = 0.03), thyroid volume (p = 0.01) and Dmean (p = 0.03) appeared to be correlated with hypothyroidism in univariate analysis. However, there was not association found in multivariate analysis for these factors. Conclusions: Thyroid disorders after radiation therapy to the neck still represent a clinically underestimated problem. V30 may be a useful tool for evaluating the risk of hypothyroidism when determining an individual patient's treatment.
Keywords: Dosimetric analysis; Hypothyroidism; Radiotherapy; HEAD; CANCER; CARCINOMA; LARYNGEAL; LYMPHOMA; TUMORS